Occupational Risks of Health Professionals in Turkey as an Emerging Economy - Nilgun Ulutasdemir; Metin Cirpan; Ebru Ozturk; Ferdi Tanir (Ubiquity Press, 2015)
Background: Health services are one of the work areas that contain important risks in terms of the occupational health and safety of the laborer. Professionals in various areas of health services encounter biological, chemical, physical, ergonomic, and psychosocial risks, particularly in hospitals. Objectives: This study has been performed to evaluate the impacts of the occupational risks on health of health professionals in Turkey. Findings: In Turkey, as an emerging economy, the history of studies on health professionals is not longstanding. There have been various regulations intended for the occupational health and safety of health professionals in line with the Regulation of the Provision on Patient and Staff Safety prepared in 2012. However, applications can differ from region to region, institution to institution, and person to person. Conclusions: We believe that this review will lead health professionals to be aware of occupational risks and contribute to planning health services for health professionals.